Editorial: non‐invasive testing for EoE—does microbiome testing hold the key? Authors' reply. Issue 4 (25th July 2022) - Facchin, Sonia; Calgaro, Matteo; Pandolfo, Mattia; Caldart, Federico; Ghisa, Matteo; Vitulo, Nicola; Savarino, Edoardo Vincenzo
Abstract : LINKED CONTENT This article is linked to Facchin et al papers. To view these articles, visit https://doi.org/10.1111/apt.17091 and https://doi.org/10.1111/apt.17130